71.5k views
3 votes
Given the following coordinates complete the reflection transformation.​

Given the following coordinates complete the reflection transformation.​-example-1

2 Answers

1 vote

Answer:

see explanation

Explanation:

Under a reflection in the x- axis

a point (x, y ) → (x, - y ) , then

A (2, 0 ) → A' (2, 0 )

B (4, 1 ) → B' (4, - 1 )

C (6, - 4 ) → C' (6, 4 )

Under a reflection in the y- axis

a point (x, y ) → (- x, y ) , then

A' (2, 0 ) → A'' (- 2, 0 )

B' (4, - 1 ) → B'' (- 4, - 1 )

C' (6, 4 ) → C'' (- 6, 4 )

User I Z
by
4.7k points
4 votes
A(-0,-2) B(-1,-4) C(4,-6)
User Zmccord
by
5.0k points